2009
DOI: 10.3892/or_00000282
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 by CTCE-9908 inhibits breast cancer metastasis to lung and bone

Abstract: Abstract. Metastasis occurs, in part, due to tumor cell responses to chemokine secretion by ectopic organs or tissues. SDF-1 is constitutively expressed in tissues where metastases frequently develop while breast carcinoma cells express the receptor for SDF-1, CXCR4, which is correlated with increased bone metastasis and poor overall survival. We hypothesized that treatment with a CXCR4 antagonist, CTCE-9908, would decrease incidence of bone and lung metastasis. Treatment with CTCE-9908 (25 mg/kg) began the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…CTCE-9908 inhibits human breast tumor cells growth in mouse xenografts impairing the CXCR4–VEGF loop and lowering tumor VEGF levels (Hassan et al, 2011) and affects breast, prostate and esophageal cancer metastasization in murine models (Wong and Korz, 2008; Richert et al, 2009). Phase I/II clinical trials of this compound, in patients with hepatocellular carcinoma, are currently under evaluation (Wong and Korz, 2008).…”
Section: Targeting Cxcl12–cxcr4/cxcr7 Axis In Cancer: Rationalementioning
confidence: 99%
“…CTCE-9908 inhibits human breast tumor cells growth in mouse xenografts impairing the CXCR4–VEGF loop and lowering tumor VEGF levels (Hassan et al, 2011) and affects breast, prostate and esophageal cancer metastasization in murine models (Wong and Korz, 2008; Richert et al, 2009). Phase I/II clinical trials of this compound, in patients with hepatocellular carcinoma, are currently under evaluation (Wong and Korz, 2008).…”
Section: Targeting Cxcl12–cxcr4/cxcr7 Axis In Cancer: Rationalementioning
confidence: 99%
“…CTCE-9908 shows a potent inhibitory activity in metastasis . Higher doses (25 mg/kg/mouse or more) than those used in these studies , may be necessary to inhibit metastasis. These findings strongly suggest that the antimetastatic effect of CTCE-KLAK is due to the cytotoxic ability of the KLAK motif.…”
Section: Discussionmentioning
confidence: 86%
“…For example, CTCE-9908 is a 17 amino acid peptide that consists of a dimer for the first eight amino acids of SDF-1α. CTCE-9908 competitively inhibits the interaction between the CXCR4 receptor and its ligand SDF-1α. CTCE-9908 blocks the function of CXCR4, thus suppressing tumor growth and metastasis in different mouse tumor models. …”
Section: Introductionmentioning
confidence: 99%
“…OBs constitutively express CXCL12 and attract CXCR4-expressing tumor cells (14). Using mouse models, it has been shown that breast, lung, and prostate cancer cells overexpressing CXCR4 and CXCR7 increased their ability to extravasate and colonize bone (15, 16), and CXCR4 inhibition decreased bone and lung metastases (17, 18). Integrins and cadherins are other crucial factors for the interactions between DTCs and niches (16, 19).…”
Section: Dtcs Colonize Bone Marrow and Activate The Bone Metastatic Vmentioning
confidence: 99%